Phytochemical screening, proximate composition, and antihyperlipidemic activity of the barley-rich nutraceutical combination in triton X-100-induced hyperlipidemic Wistar rats - Samreen M. Sheik, Karkala Sreedhara Ranganath Pai, B. S. Mamatha, H. Madhukar Mallya, Vani Lakshmi Ramesh Iyer, Varashree Bolar Suryakanth, Deepak Nayak Manel, Pallavi Mahesh Shettigar, Revathi P. Shenoy (Journal of Applied Pharmaceutical Science, 2023)
Cardiovascular disorders are associated with hyperlipidemia, and statin therapy is the first line of treatment, with several side effects. To prevent hyperlipidemia and for cost-effectiveness with no side effects, the study aimed to develop a nutraceutical recipe. For 15 days, the Wistar rats were fed an oral diet supplemented with barley, foxtail millet, flaxseeds, moong, and fish oil. Each rat was treated with Triton X-100 intraperitoneally to induce hyperlipidemia. The serum lipid profiles were measured. Diet formulations rich in flaxseeds and barley significantly improved high-density lipoprotein levels in rats and reduced total cholesterol, triglycerides, and low- and very low-density lipoprotein levels. Fish oil, foxtail millet, and moong did not affect high-density lipoproteins. Our next step was to combine the nutraceuticals and test them similarly to the above, along with analyzing the lipid profiles. It was found that the barley-rich combination reduced cholesterol most effectively among the four different combinations tested. Furthermore, alkaloids, carbohydrates, proteins, steroids, and cardiac glycosides were identified by phytochemical analysis. The proximate analysis revealed the presence of 30% moisture, 6% ash, 46% carbohydrate, 10% protein, 5% fat, and 1% fiber. The study concludes that the barley-rich nutraceutical combination is beneficial in preventing hyperlipidemia.